Changes in perceived knowledge about childbirth among pregnant women participating in the Senses of Birth intervention in Brazil: a cross-sectional study - Luísa M. M. Fernandes; Sônia Lansky; Bernardo J. Oliveira; Amélia A. L. Friche; Christine T. Bozlak; Benjamin A. Shaw (BMC, 2020)
Abstract Background Senses of Birth (SoB) is a health education intervention in Brazil that aims to reduce unnecessary cesareans in the country by providing information on reproductive rights, benefits and risks of childbirth, and use of intrapartum evidence-based practices (EBP) which are recommended by the World Health Organization (WHO) to improve childbirth outcomes and satisfaction. This study evaluates the impact of the SoB on pregnant women's perceived knowledge about normal birth (NB), cesarean, and use of EBP. Methods 1287 pregnant women answered a structured survey immediately after their visit to the intervention, between March 2015 and March 2016. To estimate the potential impact of the intervention on women's perceived knowledge, and possible associations between sociodemographic characteristics and perceived knowledge, statistical analyses were performed, including paired T-tests, ANOVA, and logistic and linear regressions. Results The mean score (MS) of perceived knowledge after the intervention was higher than the MS before experiencing the intervention for all three knowledge domains: Normal Birth (MS Before = 3.71 x MS After = 4.49), Cesarean (MS Before = 3.54 x MS After = 4.26) and EBPs (MS Before = 3.14 x MS After = 4.14). The results suggest that perceived knowledge increased more for low-income women (B = 0.206; p < 0.001 for EBP), women without private health insurance (OR 2.47, 95% CI: 1.49-4.09 for NB), with private prenatal care (OR 2.42, 95% CI: 1.59-3.66 for NB), experiencing their first pregnancy (OR 1.92, 95% CI: 1.31-2.82 for EBP; OR 1.37, 95% CI: 1.03-1.84 for NB; OR 1.37, 95% CI: 1.03-1.84 for cesarean), and in their first or second trimester (OR 1.64, 95% CI: 1.13-2.39 for EBP; OR 1.48, 95% CI: 1.11-1.97 for NB; OR 1.85, 95% CI: 1.40-2.41 for cesarean). Conclusion The study showed that participation in the SoB was associated with an increase in perceived knowledge among Brazilian pregnant women. The intervention gains relevance considering the lack of evidence of the impact of non-clinical interventions to reduce unnecessary cesareans in middle and low-income countries.